Juridical Review of Restorative Justice in the Juvenile Justice System through Diversion - Claudia Carolina Indra Putri (IJCLS (Indonesian Journal of Criminal Law Studies), 2019)
Children are the most valuable assets, for families, communities and nations so that they need to be protected and noticed from negative influences especially in the current era of globalization. This is because children at the age of 12-18 years are still easily affected by negative factors outside themselves so that children fall into juvenile delinquency and even lead to criminal acts which are then called children who conflict with the law. Children who have committed a crime will inevitably bring into the criminal justice process which causes children to be harmed because it will create a negative stigma on children, discrimination, loss of children's rights and so on. For this reason, there is a need for other ways of solving child cases through the diversion stage with a restorative justice approach. The research method used is a normative juridical legal research method, the approach used in legal research is the statute approach. The results and discussion of diversion in the criminal justice system is the process of resolving child cases out of criminal justice. Diversion must be applied during the investigation / investigation phase, the prosecution stage, and the examination phase in the court. In Indonesia diversion embodied in Law No. 11 of 2012 concerning the Criminal Justice System of Children in the implementation of diversion is very suitable to be combined with a restorative justice approach which is the settlement of criminal cases involving the perpetrators, victims, families of perpetrators / victims, and other parties related parties to jointly seek a just solution by emphasizing recovery back to its original state, and not retaliation.